Optimizing Energy Management in Hybrid Systems: A Case Study on PV, Battery, and Hydrogen Electrolysis - Rada, Rawan A; Anwar, Naveed; Hussein, Aziza I.; M. Aly, Rabab Hamed (IAES Indonesian Section, 2025)
Energy-intensive facilities face significant challenges in managing energy costs while ensuring reliable power for critical operations. This paper explores the integration of renewable energy and hydrogen technologies in a hybrid system, aimed at reducing grid dependency, minimizing energy costs, and contributing to environmental sustainability. A hybrid energy system comprising solar photovoltaic (PV) generation, battery storage, hydrogen production via electrolysis, and a proton exchange membrane (PEM) fuel cell was developed and simulated using MATLAB Simulink. The system was controlled by an intelligent energy management system (EMS) based on fuzzy logic, which dynamically prioritized energy sources to ensure operational autonomy. A hospital in Jeddah is used as a case study to demonstrate the application of this hybrid system. Simulation results showed that the hybrid system could generate up to 3,017,359 kWh annually, reducing the cost of energy (COE) from 0.19/kWh to 0.11/kWh. The system alleviated grid load by 3,000,000 kWh/year and reduced CO₂ emissions by 1.5 million kg annually. The PV array demonstrated a maximum power point tracking (MPPT) efficiency of 93.6%, and the PEM fuel cell achieved an efficiency of 65%. The fuzzy logic EMS effectively optimized energy flow, ensuring reliable power supply without frequent reliance on grid power. These findings highlight the potential of hybrid renewable energy systems for enhancing energy resilience and sustainability in energy-intensive facilities.